2015
DOI: 10.2196/jmir.2988
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Program to Increase Knowledge and Reduce Cigarette and Nargila Smoking Among Arab University Students in Israel: Mixed-Methods Study to Test Acceptability

Abstract: BackgroundAmong Arab citizens in Israel, cigarette and nargila (hookah, waterpipe) smoking is a serious public health problem, particularly among the young adult population. With the dramatic increase of Internet and computer use among Arab college and university students, a Web-based program may provide an easy, accessible tool to reduce smoking rates without heavy resource demands required by traditional methods.ObjectiveThe purpose of this research was to examine the acceptability and feasibility of a pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 30 publications
5
40
0
Order By: Relevance
“…Similarly, Asfar and colleagues (Asfar, Al Ali, Rastam, Maziak, & Ward, 2014) documented promising 3-month abstinence rates (30 and 44%) in response to both brief (1 in-person, 3 phones sessions) and intensive (3 in-person, 5 phone sessions) WP interventions, respectively. Finally, in an uncontrolled online study, Essa-Hadad and colleagues (2015) found that participants decreased WP smoking from baseline to one-month follow-up in response to video- and text-based health information. Collectively, these data show promise for WP-specific interventions.…”
mentioning
confidence: 99%
“…Similarly, Asfar and colleagues (Asfar, Al Ali, Rastam, Maziak, & Ward, 2014) documented promising 3-month abstinence rates (30 and 44%) in response to both brief (1 in-person, 3 phones sessions) and intensive (3 in-person, 5 phone sessions) WP interventions, respectively. Finally, in an uncontrolled online study, Essa-Hadad and colleagues (2015) found that participants decreased WP smoking from baseline to one-month follow-up in response to video- and text-based health information. Collectively, these data show promise for WP-specific interventions.…”
mentioning
confidence: 99%
“…Recently, a feasibility study tested the effect of web-based intervention aimed to increase knowledge and reduce cigarette and nargila smoking among Arab university students, of whom one-fifth were smokers. The intervention was well-accepted, increased the proportion of students in the contemplation phase, but was not associated with cigarette smoking cessation after 1 month [45]. We are not aware of other studies evaluating the efficacy of smoking prevention/cessation interventions among low SES groups, immigrants and ethnic minority groups in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…The studies showed that the interventions were contextualised for these continents and settings. Of the 10 studies, 7 focused on the efficacy of the intervention, [27][28][29][30][31][32][33] 2 on the feasibility of the intervention, [34,35] and 1 on describing the intervention. [36] Fifty percent (n=5) of the studies were of randomised controlled design, 30% (n=3) pre-test and post-test design, and 20% (n=2) quasi-experimental design.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…[27,29] The reasons for focusing on adolescents were that the period of adolescence has been identified as a higher risk factor for hookah pipe use than any other age group [29] and that smoking often starts during adolescence. [27] Some studies focused on adult smokers and included college or university students [30,33,35] and adults. [28,31,32,34,36] Table 2 describes each intervention in terms of the RE-AIM framework.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation